2016
DOI: 10.1039/c6fo00400h
|View full text |Cite
|
Sign up to set email alerts
|

Potential allergenicity response to structural modification of irradiated bovine α-lactalbumin

Abstract: Bovine α-lactalbumin (α-La) is a major food allergen found in milk and is characterized by high conformational stability because of its four disulfide bridges and being calcium bound. This study aimed to describe the influence of gamma irradiation on the structure and potential allergenicity of α-La. The prepared α-La was irradiated at doses of 1-10 kGy. The changes in structure were characterized through SDS-PAGE, circular dichroism spectroscopy, ultraviolet absorption spectroscopy, and fluorescence spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…As an important marker of immediate‐type hypersensitivity in the BALB/c mouse models, serum histamine level reflects the degree of degranulation of basophils and mast cells 18,26 . Reasonably, our findings revealed that mast cells in TM‐sensitized mice were degranulated and promoted allergy, which is also supported by the work of other researchers 19 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As an important marker of immediate‐type hypersensitivity in the BALB/c mouse models, serum histamine level reflects the degree of degranulation of basophils and mast cells 18,26 . Reasonably, our findings revealed that mast cells in TM‐sensitized mice were degranulated and promoted allergy, which is also supported by the work of other researchers 19 …”
Section: Discussionsupporting
confidence: 86%
“…Cell models, such as human basophil and mast cells, have been successfully used to investigate the mechanisms of allergenicity. Basophils are important immune cells used to define food allergy by measuring the levels of β ‐hexosaminidase and histamine, 19,20 which are important indicators of the degranulation of basophils. The activity of basophils and the degree of degranulation are positively correlated with allergenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The peptides with low MW were analyzed using tricine‐SDS‐PAGE with 4%, 10%, and 16.5% acrylamide. The gels were immersed in a fixative solution containing ethanol, acetic acid, and water (4:1:5, v/v/v) for 30 min …”
Section: Methodsmentioning
confidence: 99%
“…The gels were immersed in a fixative solution containing ethanol, acetic acid, and water (4:1:5, v/v/v) for 30 min. 18 The gel was stained with Coomassie Brilliant Blue (R-250) and destained with destain buffer (acetic acid: methanol: water =3:2:31, v/v). Subsequently, the gel was scanned using a SQ-GS800 scanning densitometer (Bio-Rad Laboratories, USA).…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (Smentioning
confidence: 99%
“…Basophils are the important cell involved in allergic reactions (Rosenwasser & Boyce, 2003). KU812 cells had been used for evaluation of the allergenicity of α‐LA successfully (Meng, Li, Wang, et al, 2016). KU812 cells were also used for evaluation of the allergenicity of peanut successfully (Zhang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%